Kepuasan Orang Tua Terhadap Pelayanan Keperawatan di Ruang Perinatologi - Erna Julianti; Fajar Tri Waluyanti; Allenidekania Allenidekania (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2018)
The Parents' satisfaction of premature babies is very important as one of the basic steps in determining the quality of nursing service. This study aims to identify parental satisfaction in the perinatology. Consecutive sampling technique was conducted to select 59 parents of premature babies as research respondents. Instrument in this study uses EMPATHIC N. The data was analyzed with Pearson test. The results showed that the average of premature babies’ care score was 161.93 and the average of parents’ satisfaction score was 280.07. Nursing care should be evaluated to improve the performance of nurses and the quality of care of premature babies and parents’ satisfaction.